Effects of different types of milk consumption on type 2 diabetes and the mediating effect of AA: A Mendelian randomization study of East Asian populations - Qing-Ao Xiao; Lin Chen; Xiao-Long Li; Qiang Han; Hai-Tao Li; Xiao-Ling Zhang (Journal of Dairy Science)
ABSTRACT: There is currently a lack of research examining the association between the consumption of different dairy products and type 2 diabetes (T2D) in East Asian populations. To address this gap, the present study employs Mendelian randomization to investigate the potential effects of 3 different types of milk consumption (including whole milk, semi-skim milk, and skim milk) on the risk of developing T2D. The results indicate that both whole milk and skim milk are associated with an increased risk of T2D (whole milk: odds ratio [OR] = 1.022, 95% CI: 1.001–1.044; skim milk: OR = 1.023, 95% CI: 1.007–1.039). Mediation analysis revealed that asparagine acts as a mediator between skim milk consumption and T2D, with a mediation effect of 0.003 (95% CI: 0.000 to 0.008), accounting for 14.269% of the total effect.